2015
DOI: 10.1371/journal.pone.0119424
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Sentence Production Abilities and Their Relation to Working-Memory Capacity: Evidence from a Verb-Final Language

Abstract: ObjectivesThis study investigated the best predictor to capture age-related changes in passive-sentence production using a constrained sentence-production paradigm and explored the role of working-memory capacity in relation to the task demands of the sentence-production tasks.MethodsA total of 60 participants participated in the study ranging in age from 21 to 86. All were administered a syntactic-priming and a sentence-completion task under either canonical or noncanonical word-order conditions.ResultsAge wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
1
29
0
6
Order By: Relevance
“…While no studies to date have examined age-related effects on onset latency priming, a few studies have investigated age effects on choice syntactic priming. However, this has produced mixed results with two studies finding preserved priming of passives in older adults (Hardy et al, 2017(Hardy et al, , 2019, while others have not (Heyselaar et al, 2017, footnote 2;Sung, 2015Sung, , 2016). 2 It is therefore difficult to make direct hypotheses about age-related effects on onset latency syntactic priming based on previous evidence.…”
Section: Experiments 1 Examining the Effect Of Aging On Latency Measurmentioning
confidence: 98%
“…While no studies to date have examined age-related effects on onset latency priming, a few studies have investigated age effects on choice syntactic priming. However, this has produced mixed results with two studies finding preserved priming of passives in older adults (Hardy et al, 2017(Hardy et al, , 2019, while others have not (Heyselaar et al, 2017, footnote 2;Sung, 2015Sung, , 2016). 2 It is therefore difficult to make direct hypotheses about age-related effects on onset latency syntactic priming based on previous evidence.…”
Section: Experiments 1 Examining the Effect Of Aging On Latency Measurmentioning
confidence: 98%
“…It therefore remains unclear whether linguistic priming effects would continue to be observed in older adults in a task in which demands are increased (e.g., by manipulating the codability of the nouns). Moreover, the consideration of task demands vs. cognitive supply may also be necessary for clarifying the mixed findings within the existing choice syntactic priming and aging literature (Hardy et al, 2017;Heyselaar et al, 2017Heyselaar et al, , 2018Sung, 2015). There are minimal methodological differences between the various studies (e.g., all used a picture description production task); however, it remains possible that differences in the characteristics of the samples, such as education level and native language use, may have resulted in differences in processing efficiency of the older adult groups, leading to different behavioral findings between studies (Peelle, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While no studies to date have examined agerelated effects on onset latency priming, a few studies have investigated age effects on choice syntactic priming. However, this has produced mixed results with two studies finding preserved priming of passives in older adults (Hardy, Messenger, & Maylor, 2017;Heyselaar, Wheeldon, & Segaert, 2018), while others have not (Heyselaar, Segaert, Walvoort, Kessels, & Hagoort, 2017, footnote 2;Sung, 2015). 2 It is therefore difficult to make direct hypotheses about age-related effects on onset latency syntactic priming based on previous evidence.…”
Section: Examining the Effect Of Aging On Latency Measures Of Syntax mentioning
confidence: 99%
“…Our motivation for examining the nominative-initial preference in Korean came from evidence regarding aging populations. Previous studies consistently reported that elderly adults demonstrated greater difficulties in non-nominative-initial word-order than nominative-initial structures across modalities; including a sentence comprehension task using a pictogram-based sentence-picture paradigm with full case markings (Sung, 2015a;2017), a sentence production task (Sung, 2015b), and a case marker processing task (Sung, 2017). The consistent findings that, despite the freedom of word order in Korean, normal elderly adults have greater difficulties with non-nominative-initial Because previous studies have showed that Korean-speaking elderly adults have more difficulty comprehending passive sentences than active sentences (Sung, 2015a(Sung, , 2017, we also manipulated the syntactic voice of sentences to present active and passive verbal forms following the NPs.…”
mentioning
confidence: 99%